The power of storytelling in our lives - Abdul Razak, Mohd Abbas; Mustapha, Maziah (Department of Communication, Kulliyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), IIUM, 2024)
From ancient to modern times, humanity has used storytelling as a tool to pass on values, legacy, advice, personal experience, and cultural heritage. Storytelling plays a dominant role in human lives. As human beings, and as the best creation of God Almighty, we are endowed with the gift of language to articulate our emotions. Before the modern age, through face-to-face oral presentations, we could only convey our stories to those around us. But now, with advancements in science and technology, we can reach out to a great number of listeners around the globe. As social animals, it is natural for us to share our stories with others.